Off the main lines a photographic odyssey - Hofsommer, Donovan L. (Railroads past and present, 2013)
"In this visually stunning and comprehensive photographic essay, railroad historian and photographer Donovan L. Hofsommer records the end of branchline passenger service, the demise of electric railroads, the transition from steam to diesel power, as well as the end of common carrier freight service on the Colorado narrow gauge. Off the Main Line carries readers along out-of-the-way railways in Iowa, Minnesota, Missouri, Colorado, Oklahoma, Texas, Montana, and South Dakota to see the changes that occurred on these lines from the 1940s to the 1990s"-Provided by publisher.